Pemanfaatan Tabungan Haji Dan Umrah Bank Muamalat Oleh PT. Sabrina Al-Fikri Dalam Menjaring Nasabah Di Kota Medan - Uswah Hasanah; Mutiah Khaira Sihotang (Faculty of Islamic Religion, Universitas Muhammadiyah Sumatera Utara, 2021)
Bank Muamalat Indonesia, This study aims to find out more about how the use of Hajj and Umrah savings at Bank Muamalat Indonesia Medan Sudirman Branch by PT. Sabrina Al-Fikri in attracting customers in Medan City. The long term of this research is to determine the professionalism of tours and travel, especially in the implementation of Umrah, identify how travel owners work in serving customers. The specific target to be achieved in this study is to examine the results of using Hajj and Umrah savings in serving customers. This research uses a descriptive-qualitative research type. Coupled with a valid data source about the profile of Bank Muamalat Indonesia. Place of research in the office of PT. Sabrina Al-Fikri Patriot Street, Patriot Garden Complex, Medan Sunggal District, Medan. Data collection techniques, namely by interview, observation and documentation study. Data analysis is by means of reduction, display data and verification. The final stage is done by data triangulation which is strengthened by membercheck.